Kemampuan Menulis Puisi Bebas Menggunakan Media Gambar Pada Siswa SMPK Santo Aloysius - Hawiah Djumadin; Rosa Dalima Bunga; Maria Magdalena Rini (research, training and philanthropy institution Natural Aceh, 2020)
Abstract: This study aims to determine the ability to write free poetry using picture media in VII grade students of St. Aloysius Lengko Middle School, Golo Wangkung Village, Sambi Rampas District, East Manggarai Regency. The formulation of the problem in this research is how is the ability to write free poetry using picture media in VII grade students of St. Aloysius Lengko Middle School, Golo Wangkung Village, Sambi Rampas District, East Manggarai Regency? This type of research is quantitative descriptive. The sample in this study amounted to 40 students. Data collection techniques in the form of tests and documentation. The instrument used was a test sheet. The theory used is the theory of writing poetry, theory of learning strategies and learning evaluation theory. The results of the study of the ability to write poetry by using media images in students of the St. Aloysius Lengko Middle School VII class as a whole are classified as good with an average achievement of 77.47%. Completed students numbered 31 people with a percentage of 77.5%. While students who did not complete a total of 9 people with 22.5% presentse. Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan menulis puisi bebas menggunakan media gambar pada Siswa kelas VII SMPK Santo Aloysius Lengko Ajang Kelurahan Golo Wangkung, Kecamatan Sambi Rampas, Kabupaten Manggarai Timur. Rumusan masalah dalam penelitian ini adalah bagaimanakah kemampuan menulis puisi bebas menggunakan media gambar pada Siswa kelas VII SMPK Santo Aloysius Lengko Ajang Kelurahan Golo Wangkung, Kecamatan Sambi Rampas, Kabupaten Manggarai Timur? Jenis penelitian ini adalah deskriptif kuantitatif. Sampel dalam penelitian ini berjumlah 40 orang siswa. Teknik pengumpulan data berupa tes dan dokumentasi. Instrument yang digunakan adalah lembar tes. Teori yang digunakan adalah teori menulis puisi, teori startegi belajar mengajar dan teori evaluasi pembelajaran. Hasil penelitian kemampuan menulis puisi dengan menggunakan media gambar pada siswa SMPK Santo Aloysius Lengko Ajang kelas VII secara keseluruhan tergolong baik dengan rata-rata pencapaian 77,47%. Siswa yang tuntas berjumlah 31 orang dengan presentase 77,5%. Sedangkan siswa yang tidak tuntas bejumlah 9 orang dengan presentse 22,5%.